GIS-based site selection and dynamic modelling of Magallana oyster in the Sado Estuary, Portugal - Gomes, Diogo Filipe Prata (2019)
A case study was developed to assess the viability of Portuguese oyster (Magallana angulata) and Pacific oyster (Magallana gigas) aquaculture in the Sado Estuary, Portugal. It applies an integrative methodology for site selection of shellfish aquaculture, complemented with a farm-scale carrying capacity model to evaluate production, environmental effects and socio-economic outputs. The site selection methodology uses a Multi Criteria-Evaluation (MCE) through Geographic Information Systems (GIS) software. When combined, both tools generate a holistic overview of aquaculture opportunities to support strategic planning decisions. The used MCE in this study, considers suitability factors based on water quality and food sources, as well as subsequent factors describing socio-economic and product quality suitability. Combining these to the regulatory and spatial constraints in the study area, a final site selection map was generated, screening out suitable areas for aquaculture. The dynamic model, FARM – Farm Aquaculture Resource Management, was later applied to the identified suitable areas for aquaculture practice, where the production and environmental effects of two different locations were estimated and compared at a farm-scale level. This methodology illustrates how GIS-based models may be used in conjunction with farm-scale carrying capacity models to assist decision-makers in developing a sustainable approach to aquaculture.